لسه عم تسجل - Al Batal, Saeed; Ayoub, Ghiath (Syria ; Lebanon ; France ; Germany ; Qatar : Ramonda Ink SAS, 2018)
Saeed is a young cinema enthusiast in Eastern Ghouta, Syria, teaching other young people the rules of filming. The realities they face, however, are too harsh for rules. His friend Milad is finishing his studies in Fine Arts on the other side of the fence, in Damascus, under the control of the regime. At one point, Milad decides to leave the capital and join Saeed in besieged Douma, where they set up a local radio station and film studio. They film everything, until one day the camera films them…
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films